Réponses

2014-10-15T21:38:52+02:00
1) g(1) = 2x-1 = -2 
donc g(1) = -2
2) g(2) = 2x-2 = -4
donc g(2) = -4
3) g(-4) = 2x-4 = -8
donc g(-4) = -8
4) g(-3,5) = 2x-3,5 = -7
donc g(3,5) = -7
2014-10-15T21:43:44+02:00
a = 1
g(a) = 1/a = 1
b = 2
g(b)  = 1/b = 0,5
c = -4 
g(c) = 1/c = -0,25
d = -1,5
g(d) = 1/d = 1/-1,5 = -0,666666666666667
Merci beaucoup
Non erreur je reprends le problème il s'agit du double de l'inverse
Comment ?
a = 1
g(a) = 2(1/a) = 2
b = 2
g(b) = 2(1/b) = 1
c = -4
g(c) = 2(1/c) = -0,5
d = -1,5
g(d) = 2(1/d) = 2/-1,5 = -1,33333333333333